The Value of NOTCH2NLC Gene Detection and Skin Biopsy in the Diagnosis of Neuronal Intranuclear Inclusion Disease - Pang, Jie; Yang, Jing; Yuan, Yanpeng; Gao, Yuan; Shi, Changhe; Fan, Shiheng; Xu, Yuming (Frontiers in Neurology, 2021)
Neuronal intranuclear inclusion disease (NIID) is characterized by the presence of eosinophilic nuclear inclusion bodies. The clinical manifestations of NIID are heterogeneous, and its diagnosis based on imaging alone is difficult. The detection of ubiquitin-positive nuclear inclusion bodies using skin biopsy is important for diagnosis; however, some trinucleotide duplication diseases manifest similar clinical characteristics, imaging features, and inclusion bodies. Latest research reported that abnormal GGC repeat amplification in NOTCH2NLC may be associated with NIID pathogenesis. Thus, the purpose of this study is to compare imaging features, skin biopsy, and the abnormal GGC repetition in NOTCH2NLC for the diagnosis of NIID. Skin biopsy was performed in ten patients with clinical and imaging manifestations of NIID to detect ubiquitin-positive nuclear inclusion bodies. The number of CGG repeats of FMR1 was determined to exclude fragile X-associated tremor/ataxia syndrome. Repeat primed polymerase chain reaction was used to detect GGC in NOTCH2NLC. Finally, we analysed the clinical and imaging manifestations as well as skin biopsy and genetic test results of patients with confirmed NIID. We found that the clinical manifestations of five cases of NIID were heterogeneous, with autonomic dysfunction being the most common (5/5) manifestation. Four patients showed linear hyperintensity at the cortex-medullary junction in diffusion-weighted imaging (DWI). Patients with NIID showed ubiquitin-positive nuclear inclusion bodies (5/5) and exhibited abnormal GGC repeat amplification in NOTCH2NLC (5/5). The typical DWI results were highly consistent with skin biopsy results (P = 0.048, K = 0.8); likewise, genetic testing and skin biopsy showed approximately similar results (P = 0.008, K = 1). These results indicate diagnostic consistency in skin biopsy and abnormal GGC repeat amplification in NOTCH2NLC. Therefore, the NOTCH2NLC gene test may be used as an alternative to skin biopsy to diagnose NIID.